PENGARUH CONTENT MARKETING TERHADAP CUSTOMER ENGAGEMENT PADA INSTAGRAM @DEARMEBEAUTY (PT GARLAND CANTIK INDONESIA) - Rossanhaz Syah; Lina Auliana; Rivani (JURNAL LENTERA BISNIS, 2024)
This study aims to analyze the influence of content marketing on customer engagement on the Instagram account @dearmebeauty managed by PT Garland Cantik Indonesia. Instagram is a popular social media platform used as a marketing channel. The research data was collected through questionnaires distributed to 122 respondents who follow the @dearmebeauty Instagram account and have purchased products from Dear Me Beauty at least twice. The results of the analysis show that content marketing has a significant influence on customer engagement. The implications of this study are the importance for companies to design and deliver engaging and relevant content to enhance customer engagement. Effective content marketing strategies can increase customer loyalty and help companies achieve marketing goals more efficiently.